Bilirubin and atherosclerotic diseases - Vítek, L (Physiological research, 2017)
Bilirubin is the final product of heme catabolism in the systemic circulation. For decades, increased serum/plasma bilirubin levels were considered an ominous sign of an underlying liver disease. However, data from recent years convincingly suggest that mildly elevated bilirubin concentrations are associated with protection against various oxidative stress-mediated diseases, atherosclerotic conditions being the most clinically relevant. Although scarce data on beneficial effects of bilirubin had been published also in the past, it took until 1994 when the first clinical study demonstrated an increased risk of coronary heart disease in subjects with low serum bilirubin levels, and bilirubin was found to be a risk factor for atherosclerotic diseases independent of standard risk factors. Consistent with these results, we proved in our own studies, that subjects with mild elevation of serum levels of unconjugated bilirubin (benign hyperbilirubinemia, Gilbert syndrome) have much lower prevalence/incidence of coronary heart as well as peripheral vascular disease. We have also demonstrated that this association is even more general, with serum bilirubin being a biomarker of numerous other diseases, often associated with increased risk of atherosclerosis. In addition, very recent data have demonstrated biological pathways modulated by bilirubin, which are responsible for observed strong clinical associations.
Keywords: Humans; Oxidative Stress; biologické markery; klinické zkoušky jako téma; antioxidancia; oxidační stres; zvířata; Bilirubin; Clinical Trials as Topic; bilirubin; rizikové faktory; Atherosclerosis; Animals; Antioxidants; Risk Factors; lidé; Biomarkers; ateroskleróza